Serial Hurricanes The 2017 Hurricane Public Health Responses: Case Studies Illustrating the Role of Centers for Disease Control and Prevention's Public Health Emergency Preparedness Program. (26th May 2023) - Martinez, DeAndrea; Landon, Kelcie A.; McDermott, Wesley; Roth, Joseph; Schnall, Amy Helene; Talbert, Todd P.; Mainzer, Hugh M.
ABSTRACT: The Centers for Disease Control and Prevention (CDC), Division of State and Local Readiness (DSLR), Public Health Emergency Preparedness(PHEP) program funds 62 recipients to strengthen capability standards to prepare for and respond to public health emergencies. Recipients use these PHEP resources in addition to CDC's administrative and scientific guidance to support preparedness and response program planning and requirements. It is expected that public health agencies develop and maintain comprehensive emergency preparedness and response plans in preparation for disasters such as hurricanes. The 2017 historic hurricane season highlighted how emergency planning and collaborative operational execution is important for public health agencies to effectively prepare for and respond to both the immediate and long-term population health consequences of these disasters. In 2017, the southeastern United States (US) and US Caribbean territories experienced 3 Category 4 or higher Atlantic hurricanes (Harvey, Irma, and Maria) within a 5-week period. This paper highlights selected case studies that illustrate the contributions and impact of jurisdictional emergency management planning and operational capacity supported by capability standards during the 2017 hurricane season. Although the magnitude of the 2017 hurricanes required public health officials to seek additional assistance, the following case studies describe the use of public health preparedness systems and recovery resources supported by the PHEP program.